O‘QUVCHILARNING TEXNIK IJODKORLIGINI RIVOJLANTIRISHDA TRIZ TEXNOLOGIYASIDAN FOYDALANISHNING AFZALLIKLARI - Muxliboyev, M.Q. (SCIENCE and SOCIETY, 2025)
This article presents opinions and recommendations on reforming the process of training qualified teachers, directions, stages and methods of developing technical creativity in students of comprehensive schools, and the advantages of TRIZ technology.